1995
DOI: 10.1093/rheumatology/34.6.516
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bone Mineral Density in Women With Marfan Syndrome

Abstract: Although radiological studies suggest that Marfan syndrome is associated with osteopenia, investigations utilizing measurements of bone mass have yielded conflicting results. To address this question further, we measured bone mineral density (BMD) in 14 women with Marfan syndrome at the right hip and lumbar spine by dual energy X-ray absorptiometry (DXA). Results were compared with the age- and weight-matched reference population supplied by the DXA manufacturer, and with our own control population of normal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 0 publications
2
24
1
Order By: Relevance
“…The results of comparisons of the study of Giampietro et al [11] and the other published studies that reported actual BMD values [7][8][9][10] in male and female subjects with Marfan syndrome are summarized in Tables 1 and 2. Reduced BMD was previously reported in the femoral neck of adult men in two studies [9,10].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of comparisons of the study of Giampietro et al [11] and the other published studies that reported actual BMD values [7][8][9][10] in male and female subjects with Marfan syndrome are summarized in Tables 1 and 2. Reduced BMD was previously reported in the femoral neck of adult men in two studies [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…Analytical studies of BMD reported in the literature on adult patients with Marfan syndrome [7][8][9][10][11] were retrospectively reviewed. The following definitions for categories established by the World Health Organization for clinical characterization of BMD will be operative for this report.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations